Science, (not-)knowing, and periodical cultures - del Pilar Blanco, M (Routledge, 2024)
This essay examines the place of science, broadly conceived, across a range of nineteenth-century Mexican periodicals: a Spiritualist magazine (La Ilustración Espírita, 1872–93); religious-conservative newspapers (La Voz de México, 1870–1909 and El Defensor Católico, 1872); and a women’s magazine (Violetas del Anáhuac, 1888–1889). The distinct identities and ideological positions represented in these magazines shed light on the tensions between traditional and modern worldviews, while allowing readers to understand the different rhetorical spaces in which the debates about science’s attacks on spirituality took shape.